Evaluating listening and speaking skills in a mobile game-based learning environment with situational contexts. Issue 4 (18th May 2016) - Hwang, Wu-Yuin; Shih, Timothy K.; Ma, Zhao-Heng; Shadiev, Rustam; Chen, Shu-Yu
Abstract : Game-based learning activities that facilitate students' listening and speaking skills were designed in this study. To participate in learning activities, students in the control group used traditional methods, while students in the experimental group used a mobile system. In our study, we looked into the feasibility of mobile game-based learning activities. One experiment was carried out and the results revealed that the experimental-group students significantly outperformed the control-group students on the verbal post-test. However, the performance of the two groups was equal on the listening post-test. Two variables (the average score for the interactive jigsaw game and the number of designed cards) were found to be the most important factors for influencing students' performance in the verbal post-test. Furthermore, most students had positive perceptions toward learning activities that are supported by a mobile system. These results suggest that game-based learning activities can significantly improve students' speaking skills if driven by a mobile system. Furthermore, these results suggest that learning activities with a mobile system foster students to (1) practice speaking English as a foreign language (EFL) more frequently as well as to reflect on their speech; (2) create meaningful sentences and speak with greater accuracy and confidence; and (3) practice speaking EFL in an authentic context.